Determinants for a Successful Sémont Maneuver: An In vitro Study with a Semicircular Canal Model - Obrist, Dominik; Nienhaus, Andrea; Zamaro, Ewa; Kalla, Roger; Mantokoudis, Georgios; Strupp, Michael (Frontiers in Neurology, 2016)
Objective: To evaluate the effect of time between the movements/steps, angle of body movements as well as the angular velocity of the maneuvers in an in-vitro model of a semicircular canal (SCC) to improve the efficacy of the Sémont maneuver in benign paroxysmal positional vertigo (BPPV). Methods: Sémont maneuvers were performed on an in-vitro SCC model. Otoconia trajectories were captured by a video camera. The effects of time between the movements, angles of motion (0°, 10°, 20°, 30° below the horizontal line), different angular velocities (90, 135, 180°/s) and otoconia size (36 and 50µm) on the final position of the otoconia in the SCC were tested. Results: Without extension of the movements beyond the horizontal, the in-vitro experiments (with particles corresponding to 50 m diameter) did not yield successful canalith repositioning. If the movements were extended by 20° beyond the horizontal position, Sémont maneuvers were successful with resting times of at least 16 s. For larger extension angles the required time decreased. However, for smaller particles (36 m) the required time doubled. The angular maneuver velocity (tested between 90 and 180°/s) did not have a major impact on the final position of the otoconia. Interpretation: The two primary determinants for success of the Sémont maneuver are the time between the movements and the extension of the movements beyond the horizontal. The time between the movements should be at least 45 s. Angles of 20° or more below horizontal line (so-called Sémont ++) should increase the success rate of SM.